Non-hydrocarbon polymer surface carbon film and preparation method thereof
The oxygen-containing amorphous carbon film is constructed on the surface of non-hydrocarbon polymer materials through plasma immersion ion implantation, which solves the problems of uneven coating thickness and insufficient binding force in the existing carbon film preparation technology, and achieves efficient and uniform carbon film preparation, which improves the conductivity of the material and reduces the friction coefficient.
Patent Information
- Application Number
- CN202311078888.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
AI Technical Summary
The existing carbon film preparation technology has problems such as uneven coating thickness, insufficient bonding force, high cost, large gas consumption and poor material surface quality stability.
The plasma immersion ion implantation method is used to construct an oxygen-containing amorphous carbon film with a large conjugated structure on the surface of non-hydrogen polymer materials. The surface of the material is carbonized by bombardment by high-energy particles, and the plasma is used to remove impurity elements to increase the carbon content of SP2.
The uniformity and bonding force of the carbon film on the surface of non-hydrocarbon polymers are achieved, the conductivity of the material is improved and the friction coefficient is reduced, and the process is simple and the conditions are easy to control.
Smart Images

Figure CN119505329A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for rapid carbonization of a non-hydrocarbon polymer surface, that is, constructing a layer of oxygen-containing amorphous carbon film on the material surface by plasma injection, and belongs to the field of polymer material surface treatment. Background Art
[0002] There are many methods for polymer surface modification, such as chemical vapor deposition, atomic layer deposition and other chemical methods and physical methods such as magnetron sputtering. Polymer surfaces can be modified by various methods to make the material meet the requirements of use.
[0003] Carbon film has attracted wide attention from the industry due to its high electrical conductivity, high thermal conductivity, high lubricity and other properties. Currently, the main technologies used to prepare carbon film on polymer surface are as follows: evaporation, laser ablation, DLC (Diamond Like Carbon) film deposition, etc. These methods have their own shortcomings. The thickness of the coating obtained by evaporation is uneven, and the bonding force between the film and the substrate is not strong; laser ablation is costly, consumes a lot of gas, and the surface quality stability of the material is not very good; DLC film has the disadvantage of large internal stress in the coating. Summary of the invention
[0004] In order to solve the shortcomings of existing carbon film preparation methods, the present invention provides a carbon film on the surface of a non-hydrocarbon polymer material and a preparation method thereof, which can not only meet the requirements of film uniformity and bonding strength, but also has higher efficiency.
[0005] In one aspect, the present invention provides a non-hydrocarbon polymer surface carbon film, comprising a non-hydrocarbon polymer material as a matrix, and an in-situ generated oxygen-containing amorphous carbon film having a large conjugated structure; Preferably, the surface of the oxygen-containing amorphous carbon film having a large conjugated structure contains at least one of hydroxyl, carboxyl, and non-benzene ring carbonyl oxygen-containing functional groups; Preferably, the non-hydrocarbon polymer material includes at least one of polyetheretherketone, polyurethane, polyoxymethylene, polylactic acid, and polymethacrylic acid.
[0006] Preferably, the percentage of oxygen atoms in the oxygen-containing amorphous carbon film is 10% to 30%.
[0007] Preferably, the ratio of carbon-oxygen bonds to carbon-carbon bonds in the oxygen-containing amorphous carbon film is 10% to 40%:1.
[0008] Preferably, the surface conductivity of the carbon film on the surface of the non-hydrocarbon polymer is (0.1-2)×10 -11 S / mm.
[0009] Preferably, the carbon film on the surface of the non-hydrocarbon polymer has an absorbance of 0.2 to 0.7 in the visible light region.
[0010] Preferably, the surface friction coefficient of the oxygen-containing amorphous carbon film with a large conjugated structure decreases from 0.4 to 0.2 as the oxygen content decreases from 0.25 to 0.1.
[0011] On the other hand, the present invention provides a method for preparing a carbon film on the surface of a non-hydrocarbon polymer, wherein an oxygen-containing amorphous carbon film having a large conjugated structure is prepared on the surface of a non-hydrocarbon polymer material by plasma immersion ion implantation.
[0012] The present invention mainly adopts ion implantation to form an amorphous carbon film coating in situ on the surface of non-hydrocarbon polymer, which can improve the conductivity of the material surface and reduce the friction coefficient of the material surface, and has great potential in future applications.
[0013] The present invention proposes a simple method for constructing a layer of amorphous carbon film on the surface of a non-hydrocarbon polymer by ion implantation. Plasma immersion ion implantation (PIII) is a surface modification technology that uses high-voltage pulsed direct current to inject accelerated ions in a plasma as dopants into a suitable substrate or a target of a semiconductor chip with electrodes. It has the advantages of high efficiency and good adhesion between the coating and the substrate. When plasma immersion implantation is performed on the surface of a non-hydrocarbon polymer, high-energy particles bombard the material, causing molecular chain breakage, cross-linking, dehydrogenation, deoxidation, carbonization and other processes on the surface of the material, ultimately resulting in the formation of a graphite-like carbonized modified layer on the surface of the material. At the same time, the properties of the plasma itself will also affect the properties of the carbonized modified layer on the surface of the material.
[0014] Preferably, the plasma used in the plasma immersion ion implantation is hydrogen plasma, argon plasma, oxygen plasma and nitrogen plasma.
[0015] In the present invention, the carbon film produced after different plasmas are injected into the polymer surface has different structures and compositions (such as oxygen content and relative content of SP2 carbon). The principle is that the reducing ability of plasma on non-hydrocarbon polymers will have a significant impact on the subsequent formation process of the carbon film.
[0016] In the present invention, the mechanism of using hydrogen plasma to inject an amorphous carbon film on the surface of a non-hydrocarbon polymer is as follows: the high-energy particles generated during the ion injection process can cause a carbonization process to occur on the surface of the material; on the other hand, the reducing property of hydrogen plasma can more efficiently remove impurity elements (nitrogen, oxygen, etc.) in the carbon film during ion injection, thereby reducing the content of surface impurity functional groups and increasing the SP2 carbon content on the surface of the material.
[0017] In the present invention, the mechanism of using argon plasma to inject an amorphous carbon film on the surface of a non-hydrocarbon polymer is that the high-energy particles generated during the ion implantation process can cause a carbonization process on the surface of the material. Among them, the carbonization mechanism of the non-hydrocarbon polymer focuses on the removal of non-carbon and hydrogen elements (such as oxygen, nitrogen, etc.) on the polymer due to plasma reduction.
[0018] In the present invention, the mechanism of using oxygen plasma to inject an amorphous carbon film on the surface of a non-hydrocarbon polymer is as follows: the high-energy particles generated during the ion implantation process can cause the material surface to undergo a carbonization process, and the strong oxidizing property of the oxygen plasma makes it easy to add to the material surface, generating a large number of oxygen-containing functional groups and SP3 carbon. Among them, the carbonization mechanism of non-hydrocarbon polymers focuses on the removal of non-carbon and hydrogen elements (such as oxygen, nitrogen, etc.) on the polymer due to the plasma reduction.
[0019] Preferably, the parameters of the plasma immersion ion implantation include: the background vacuum of the ion implantation equipment is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×100Pa, the ion source power is 50~1200W, the negative voltage is 10kV~50kV, and the duty cycle is 10%~80%; the introduced gas is hydrogen, argon, oxygen or nitrogen.
[0020] Beneficial effects of the present invention: 1) The amorphous carbon film produced by the method provided by the present invention has excellent bonding strength with the substrate material, and there will be no phenomenon of coating shedding; 2) The method for preparing the carbon film on the surface of a non-hydrocarbon polymer provided by the present invention has a simple process and easily controllable conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a graph showing the light absorption results of the carbon film on the surface of a non-hydrocarbon polymer prepared in Example 1. It can be seen from the figure that the overall light absorption intensity of the samples treated in Example 1 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. H-PEEK has the strongest UV-visible light absorption, indicating that the reduction in oxygen content has a positive effect on the extension of the conjugated system. Figure 2 This is the infrared result of the carbon film on the surface of the non-hydrocarbon polymer prepared in Example 1. It can be seen from the figure that the overall infrared absorption intensity of the sample treated in Example 1 is reduced, indicating that the ion implantation process has caused damage to the surface structure of the material. At the same time, the surface of the sample after treatment has a high infrared absorption intensity at 1710cm -1 The infrared characteristic peak appears at 1710 cm-1 The infrared absorption peak is the strongest at , which indirectly illustrates that hydrogen plasma injection carbonization has the best effect, which is consistent with the results of Example 1. Figure 3 This is the surface voltage-current curve obtained by testing the carbon film on the surface of the non-hydrocarbon polymer prepared in Example 1. It can be seen from the figure that the surface conductivity of the sample obtained in Example 1 is significantly improved compared with the untreated sample, indicating that the formation of the carbon film improves the conductivity of the material surface. The surface conductivity of H-PEEK is the best, indicating that the reduction of oxygen content and the increase of SP2 carbon content are conducive to the improvement of surface conductivity. Figure 4 This is the XPS carbon fine spectrum of the carbon film on the surface of the non-hydrocarbon polymer prepared in Example 1; compared with the untreated sample, the ratio of CC bonds to CO bonds on its surface has changed significantly, indicating that the chemical composition of the material surface has changed. The better the plasma reducibility during treatment, the better its oxygen capture property, the higher the ratio of surface carbon-carbon bonds to carbon-oxygen bonds, and the higher the relative ratio of SP2 carbon and SP3 carbon. This shows that the oxygen capture performance of plasma has a significant effect on the properties of amorphous carbon films. After AR and O injection, the oxygen content on the material surface increases, indicating that during the ion injection process, the free radicals generated on the material surface will adsorb oxygen in the air. Figure 5 This is the average friction coefficient curve of the carbon film on the surface of the non-hydrocarbon polymer prepared in Example 1; the better the oxygen capture of the plasma used during treatment, the lower the friction coefficient of the material surface, indicating that the reduction of oxygen content on the carbon film surface and the increase of SP2 carbon content reduce the friction coefficient of the material surface. Figure 6 This is the light absorption result of the carbon film on the surface of the non-hydrocarbon polymer prepared in Example 2. It can be seen from the figure that the overall light absorption intensity of the samples treated in Example 3 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The absorption of the material after hydrogen plasma treatment is the strongest, indicating that its surface carbonization degree is the highest; Figure 7 This is the light absorption result of the carbon film on the surface of the non-hydrocarbon polymer prepared in Example 2. It can be seen from the figure that the overall light absorption intensity of the samples treated in Example 5 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The absorption of the material after hydrogen plasma treatment is the strongest, indicating that its surface carbonization degree is the highest; Figure 8 This is the infrared result of the carbon film on the surface of the non-hydrocarbon polymer prepared in Example 3. It can be seen from the figure that the overall infrared absorption intensity of the sample treated in Example 3 is reduced, indicating that the ion implantation process has caused damage to the surface structure of the material; Fig. 9This is the infrared result of the carbon film on the surface of the non-hydrocarbon polymer prepared in Example 3. It can be seen from the figure that the overall infrared absorption intensity of the sample treated in Example 5 is reduced, indicating that the ion implantation process has caused damage to the surface structure of the material; Figure 10-12 The infrared results of the carbon films on the surfaces of non-hydrocarbon polymers prepared in Examples 4, 5 and 6 are shown in Figures. It can be seen from the figures that the overall infrared absorption intensity of the samples treated in Examples 4, 5 and 6 is reduced, indicating that the ion implantation process has caused damage to the surface structure of the material; Figure 13-Figure 15 The light absorption results of the carbon films on the surface of non-hydrocarbon polymers prepared in Examples 4, 5, and 6 are shown in the figure. It can be seen from the figure that the overall light absorption intensity of the samples treated in Examples 4, 5, and 6 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The absorption of the material after hydrogen plasma treatment is the strongest, indicating that its surface carbonization degree is the highest. DETAILED DESCRIPTION
[0022] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0023] The present invention proposes a method for constructing an oxygen-containing amorphous carbon film coating on a non-hydrocarbon polymer surface by plasma injection, wherein the coating is formed by plasma injection. The preparation method of the oxygen-containing amorphous carbon film is exemplified below.
[0024] The non-hydrocarbon polymer material (sheet) is cleaned and dried by ultrasound. The solvent used for ultrasonic cleaning is ethanol, preferably anhydrous ethanol. An amorphous carbon film with a thickness of nanometers is constructed on the surface of the material by plasma injection.
[0025] In an optional embodiment, hydrogen plasma is used, wherein the parameters include: the background vacuum of the plasma equipment during the injection process is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×10 2 Pa, ion source power is 50-1200W, negative voltage is 0.1-50kV, and duty cycle is 10%-80%.
[0026] In an optional embodiment, argon plasma is used, wherein the parameters include: the background vacuum of the plasma equipment during the injection process is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10-2 ~5×10 2 Pa, ion source power is 50-1200W, negative voltage is 0.1-50kV, and duty cycle is 10%-80%.
[0027] In an optional embodiment, oxygen plasma is used, wherein the parameters include: the background vacuum of the plasma equipment during the injection process is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×10 2 Pa, ion source power is 50-1200W, negative voltage is 0.1-50kV, and duty cycle is 10%-80%.
[0028] In an optional embodiment, nitrogen plasma is used, wherein the parameters include: the background vacuum of the plasma equipment during the injection process is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×10 2 Pa, ion source power is 50-1200W, negative voltage is 0.1-50kV, and duty cycle is 10%-80%.
[0029] In the present invention, the surface conductivity of the carbon film on the surface of the non-hydrocarbon polymer obtained by measuring with a probe instrument is (0-1)×10 -11 S / mm. The absorbance of the carbon film on the surface of the non-hydrocarbon polymer obtained by UV-visible spectrophotometer in the visible light region is 0.2-0.7. In the present invention, the surface oxygen content of the carbon film on the surface of the non-hydrocarbon polymer obtained by XPS test is reduced from 0.25 to 0.1. The surface friction coefficient of the carbon film on the surface of the non-hydrocarbon polymer obtained by scratch test is reduced from 0.4 to 0.2.
[0030] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0031] Example 1 Step 1: Pretreatment: polish the PEEK disc with a thickness of 1.5 mm and a diameter of 12 mm; Step 2: Prepare the coating, put the sample into the ion implantation sample tray, evacuate to, and then perform ion implantation. The gas type is hydrogen, oxygen or argon. The samples obtained in the experiment are marked as H-PEEK, O-PEEK, and Ar-PEEK. The specific parameters are shown in Table 1.
[0032] Table 1 shows the plasma injection parameters in Example 1:
[0033] Example 2 The difference between Example 2 and Example 1 is that the non-hydrocarbon polymer in this example is polyurethane. The samples obtained in the experiment are marked as H-PU, O-PU, and Ar-PU. The specific parameters are shown in Table 3:
[0034] Table 3 shows the plasma injection parameters.
[0035] Example 3 The difference between Example 3 and Example 1 is that the non-hydrocarbon polymer in this example is polyoxymethylene. The samples obtained in the experiment are marked as H-POM, O-POM, and Ar-POM. The specific parameters are shown in Table 5:
[0036] Table 3 shows the plasma injection parameters.
[0037] Example 4 The difference between Example 4 and Example 1 is that the gas type in this example is hydrogen, and the different negative pressures are -10 kv and -20 kv respectively. The sample obtained in the experiment is marked as H-PEEK. The specific parameters are shown in Table 4.
[0038] Example 5 The difference between Example 5 and Example 4 is that the gas type in this example is argon, and the specific parameters are shown in Table 6.
[0039] Table 5 shows the plasma injection parameters
[0040] Example 6 The difference between Example 6 and Example 4 is that the gas type in this example is oxygen, and the specific parameters are shown in Table 7.
[0041] Table 6 shows the plasma injection parameters
[0042] Table 7 shows the composition and properties of the oxygen-containing amorphous carbon film with a large conjugated structure prepared by the present invention:
[0043] Table 8 shows the properties of the oxygen-containing amorphous carbon film with a large conjugated structure prepared by the present invention:
[0044] Example 8 The unmodified sample and the sample obtained in Example 1 were subjected to UV-visible spectrum test. The sample test range was 250-850nm. Figure 1 2 is the light absorption result diagram of the above samples. It can be seen from the figure that the overall light absorption intensity of the samples treated in Example 1 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The UV-visible relationship of H-PEEK is the strongest, indicating that the reduction of oxygen content promotes the extension of the conjugated system on the surface of the material.
[0045] Example 9 The unmodified sample and the sample obtained in Example 1 were subjected to infrared spectroscopy test. The test range of the samples was 1000-2000cm -1 . Figure 2 This is the infrared result of the above sample. It can be seen from the figure that the overall infrared absorption intensity of the sample treated in Example 1 is reduced, indicating that the ion implantation process has caused damage to the surface structure of the material. At the same time, the surface of the sample after treatment has a high absorption intensity at 1710cm -1 The infrared characteristic peak appears at 1710 cm -1 The infrared absorption peak is the strongest at , which indirectly illustrates that hydrogen plasma injection carbonization has the best effect, which is consistent with the results of Example 8.
[0046] Example 10 The surface conductivity test was performed on the unmodified sample and the sample obtained in the above Example 1. When each sample was tested, the probe spacing was 200 um. Figure 3 The surface voltage-current curve obtained from the above sample test. Compared with the untreated sample, the surface conductivity of the sample obtained in Example 1 is significantly improved, indicating that the formation of the carbon film improves the conductivity of the material surface. The surface conductivity of H-PEEK is the best, indicating that the reduction of oxygen content and the increase of SP2 carbon content are conducive to the improvement of surface conductivity.
[0047] Embodiment 11 The unmodified sample and the sample obtained in Example 1 were subjected to XPS test. Figure 4 This is the C1s carbon fine spectrum obtained from the test of the above sample. Compared with the untreated sample, the ratio of CC bonds to CO bonds on the surface of the sample obtained in Example 1 has changed significantly, indicating that the chemical composition of the material surface has changed. The better the plasma reducibility during treatment, the better its oxygen abstraction, the higher the ratio of surface carbon-carbon bonds to carbon-oxygen bonds, and the higher the relative ratio of SP2 carbon and SP3 carbon. This shows that the oxygen abstraction performance of plasma has a significant effect on the composition and properties of amorphous carbon films. After AR and O injection, the oxygen content on the surface of the material increases, indicating that during the ion implantation process, the free radicals generated on the surface of the material will adsorb oxygen in the air.
[0048] Example 12 The unmodified sample and the sample obtained in Example 1 were subjected to a reciprocating friction test. The test load of each sample was 10N and the test duration was 5 minutes. Figure 5 This is the time-friction coefficient curve obtained from the above sample test. The better the oxygen capture of the plasma used during treatment, the lower the friction coefficient of the material surface, indicating that the reduction of oxygen content on the carbon film surface and the increase of SP2 carbon content reduce the friction coefficient of the material surface.
[0049] Example 13 The unmodified sample and the samples obtained in the above Examples 2 and 3 were subjected to UV-visible spectrum testing. The sample testing range was 250-850nm. Figure 6-7 is the light absorption result diagram of the above samples. It can be seen from the figure that the overall light absorption intensity of the samples treated with the samples obtained in Examples 4 and 5 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. For different non-hydrocarbon polymer materials, the light absorption capacity of the surface after hydrogen plasma treatment is the best among all treatment groups. The reduction of oxygen content on the surface of the material promotes the extension of the conjugated system on the surface of the material. This result is applicable to different non-hydrocarbon polymers.
[0050] Embodiment 14 The unmodified sample and the samples obtained in Examples 2 and 3 were subjected to infrared spectroscopy test. The test range of the samples was 500-1500cm -1 . Figure 8-9 : This is the infrared result diagram of the above samples. It can be seen from the figure that the overall infrared absorption intensity of the samples treated in Examples 2 and 3 has decreased to a certain extent, indicating that the ion implantation process has caused damage to the surface structure of the material. For different non-hydrocarbon polymer materials, the infrared characteristic peak intensity of the surface treated with hydrogen plasma is the largest, which indirectly shows that the carbonization effect of hydrogen plasma implantation is the best, which is mutually confirmed with the results of Example 11.
[0051] Embodiment 15 The unmodified sample and the samples obtained in Examples 4, 5, and 6 were subjected to infrared spectroscopy testing. The test range of the samples was 500-1500 cm -1 . Figure 10-12 This is the infrared result diagram of the above samples. It can be seen from the figure that the overall infrared absorption intensity of the samples treated by Examples 4, 5, and 6 has decreased to a certain extent, indicating that the ion implantation process has caused damage to the surface structure of the material. For different gases, as the voltage increases, the intensity of the C=O characteristic peak on the surface increases, indicating that the voltage is positively correlated with the degree of carbonization.
[0052] Example 16 The unmodified sample and the samples obtained in the above Examples 4, 5 and 6 were subjected to UV-visible spectrum test. The sample test range was 250-850nm. Figure 13-15 is the light absorption result diagram of the above samples. It can be seen from the figure that the overall light absorption intensity of the samples treated with the samples obtained in Examples 4, 5, and 6 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. For different gases, as the voltage increases, the surface light absorption capacity increases accordingly, indicating that the voltage is positively correlated with the degree of carbonization.
Claims
1. A carbon film on the surface of a non-hydrocarbon polymer, characterized in that: include: A non-hydrocarbon polymer material as a matrix and an in-situ generated oxygen-containing amorphous carbon film with a large conjugated structure; Preferably, the surface of the oxygen-containing amorphous carbon film having a large conjugated structure contains at least one of hydroxyl, carboxyl, and non-benzene ring carbonyl oxygen-containing functional groups; Preferably, the non-hydrocarbon polymer material includes at least one of polyetheretherketone, polyurethane, polyoxymethylene, polylactic acid, and polymethacrylic acid.
2. The non-hydrocarbon polymer surface carbon film according to claim 1, characterized in that: The percentage of oxygen atoms in the oxygen-containing amorphous carbon film is 10% to 30%; the ratio of carbon-oxygen bonds to carbon-carbon bonds in the oxygen-containing amorphous carbon film is 10% to 40%:
1.
3. The non-hydrocarbon polymer surface carbon film according to claim 1 or 2, characterized in that: The surface conductivity of the carbon film on the surface of the non-hydrocarbon polymer is (0.1-2)×10 -11 S / mm.
4. The non-hydrocarbon polymer surface carbon film according to any one of claims 1 to 3, characterized in that: The absorbance of the carbon film on the surface of the non-hydrocarbon polymer in the visible light region is 0.2-0.
7.
5. The non-hydrocarbon polymer surface carbon film according to any one of claims 1 to 4, characterized in that: The surface friction coefficient of the oxygen-containing amorphous carbon film with a large conjugated structure decreases from 0.4 to 0.2 as the oxygen content decreases from 0.25 to 0.
1.
6. A method for preparing a carbon film on the surface of a non-hydrocarbon polymer, characterized in that: An oxygen-containing amorphous carbon film with a large conjugated structure is prepared on the surface of a non-hydrocarbon polymer material by means of plasma immersion ion implantation.
7. The preparation method according to claim 6, characterized in that: The plasma used in the plasma immersion ion implantation is a gas plasma such as hydrogen plasma, argon plasma, oxygen plasma, etc.
8. The method for modifying the surface of a non-hydrocarbon polymer according to claim 6 or 7, characterized in that: The parameters of the plasma immersion ion implantation include: the background vacuum of the ion implantation equipment is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×10 2 Pa, the ion source power is 50-1200W, the negative voltage is 10-50kV, and the duty cycle is 10%-80%; the introduced gas is hydrogen, argon, or oxygen.